Methyl jasmonate-elicited herbivore resistance: does MeJA function as a signal without being hydrolyzed to JA? - Wu, Jinsong (Springer-Verlag, 2008)
Treatment with methyl jasmonate (MeJA) elicits herbivore resistance in many plant species and over-expression of JA carboxyl methyltransferase (JMT) constitutively increases JA-induced responses in Arabidopsis. When wild-type (WT) Nicotiana attenuata plants are treated with MeJA, a rapid transient endogenous JA burst is elicited, which in turn increases levels of nicotine and trypsin proteinase inhibitors (TPIs) and resistance to larvae of the specialist herbivore, Manduca sexta. All of these responses are impaired in plants silenced in lipoxygenase 3 expression (asLOX3) but are restored to WT levels by MeJA treatment. Whether these MeJA-induced responses are directly elicited by MeJA or by its cleavage product, JA, is unknown. Using virus-induced gene silencing (VIGS), we silenced MeJA-esterase (NaMJE) expression and found this gene responsible for most of the MeJA-cleaving activity in N. attenuata protein extracts. Silencing NaMJE in asLOX3, but not in WT plants, significantly reduced MeJA-induced nicotine levels and resistance to M. sexta, but not TPI levels. MeJA-induced transcript levels of threonine deaminase (NaTD) and phenylalanine ammonia lyase (NaPAL1) were also decreased in VIGS MJE (asLOX3) plants. Finally the performance of M. sexta larvae that fed on plants treated with JA or MeJA demonstrated that silencing NaMJE inhibited MeJA-induced but not JA-induced resistance in asLOX3 plants. From these results, we conclude that the resistance elicited by MeJA treatment is directly elicited not by MeJA but by its de-methylated product, JA. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00425-008-0690-8) contains supplementary material, which is available to authorized users.